Bipolar redox electrolyte-synergistically mediated NiCoMn-811 high-Ni ternary perovskite fluorides for advanced supercapacitors in both alkaline and neutral media. Issue 15 (8th April 2021) - Shi, Wei; Yu, Wujiang; Ding, Rui; Jia, Ziyang; Li, Yi; Huang, Yuxi; Tan, Caini; Sun, Xiujuan; Liu, Enhui
Abstract : High-Ni ternary perovskite fluorides KNCMF-811 mediated with bipolar redox electrolytes construct advanced supercapacitors in both alkaline and neutral media. Abstract : Perovskite fluorides (ABF3 ) as novel electrode materials have drawn particular attention for supercapacitors (SCs). However, the key issues such as to enhance energy storage capability, clarify charge storage mechanisms, employ different electrolyte media, examine the behavior at different temperatures, etc. are all still of great challenge. Herein, we demonstrate novel high-Ni ternary ABF3 (K1.0 Ni0.8 Co0.1 Mn0.1 F3.1, denoted as KNCMF-811) as a high-performance electrode material for advanced SCs. The optimal KNCMF-811(8 # ) candidate screened by the orthogonal experiment shows an overall superior performance, demonstrating the typical conversion mechanisms in alkaline media. By synergistically mediating an appropriate concentration (10 mM) of bipolar redox electrolytes of [Cu(NH3 )4 ] 2+ and [Fe(CN)6 ] 3− complexes for the activated carbon (AC) anode and KNCMF-811 cathode, respectively, the newly constructed AC + [Cu(NH3 )4 ] 2+ //KNCMF-811(8 # ) + [Fe(CN)6 ] 3− H-type SCs demonstrate advanced performance in both alkaline and neutral media. More importantly, the capacity degradation of the optimal AC + [Cu(NH3 )4 ] 2+ //KNCMF-811(8 # ) + [Fe(CN)6 ] 3− SCs at high temperature in alkaline media can be largely restrained by modifying the catholytes with a small amount (1.0 wt%) of the Na2 MoO4 anti-polarization additive, largely owing to the effective restraint of electrode polarization by the formation of MoO x passivation films in the KNCMF-811 (8 # ) cathode at high temperature. Overall, this work provides new insight into bipolar redox electrolyte-synergistically mediated high-Ni ternary perovskite fluorides KNCMF-811 for advanced supercapacitors in both alkaline and neutral media.